"I follow Aristotle" - Cunningham, Andrew, Dr., author.
1 online resource (xii, 180 pages)
Keywords: "This book presents a new interpretation of how and why the discovery of the circulation of the blood in animals was made. It has long been known that the English physician William Harvey (1578-1657) was a follower of Aristotle, but his most strikingly 'modern' and original discovery - of the circulation of the blood - resulted from Harvey following Aristotle's ancient programme of investigation into animals. This is a new reading of the most important discovery ever made in anatomy by one man and produces not only a radical re-reading of Harvey as anatomist, but also of Aristotle and his investigations of animals"--